Beyond the collaboration - Morgan, Jessica 1968-; Sigler, Jennifer; Whitman-Salkin, Leah ca. Gegenwart (Sternberg Press, 2018)
"How do you tell the story of a friendship? How do you trace the roots of one of the most significant cross-disciplinary unions in fashion today? Artist Sterling Ruby and fashion designer Raf Simons did just that when they sat on stage with curator Jessica Morgan at the Harvard University Graduate School of Design. Offering complimentary perspectives on a bond that has matured over the span of a decade, and a body of work that transcends boundaries, Ruby and Simons spoke with mutual respect, trust, and a deep investment in the future. This is a story, and an exchange, that is beyond collaboration"--Back cover
Text of a public interview conducted at the Harvard University Graduate School of Design, April 23, 2018
Keywords: Simons, Raf -- 1968-; Ruby, Sterling -- 1972-; Ruby, Sterling / 1972- / Interviews; Simons, Raf / Interviews; Ruby, Sterling / 1972-; Simons, Raf; Artistic collaboration; Interviews